Diploma matters : a field guide for college and career readiness - Murray, Linda, 1944- (San Francisco, CA. : Jossey-Bass, 2011)
'High school should be a gateway to a better life, not a gatekeeper. Too many students wind up with too few choices, locked in by what was decided for them by a broken system. We've been handing over a diploma that holds an empty promise. In this practical field book, readers will find a'toolkit' developed by The Education Trust. The tools in the kit help school leaders and teachers examine the current high school experience, and then develop a detailed action plan to transform curriculum so that their students are ready for college and work.'--Provided by publisher.
Includes index.
Keywords: College preparation programs -- United States; Universities and colleges -- Entrance requirements